Penerapan Model Pembelajaran Kooperatif Tipe Kancing Gemerincing untuk Meningkatkan Keaktifan dan Hasil Belajar Peserta Didik Kelas X MIA 3 SMAN 1 Bontomarannu - Afianti, Nurul Wisna; Sulastry, Taty; Alimin, Alimin (JURNAL NALAR PENDIDIKAN, 2017)
AbstractThis research is a classroom action research that aims to find out how to apply cooperative learning model talking chips type in class X MIA 3 SMAN 1 Bontomarannu on the subject matter of chemical bonding. This research was conducted in two cycles. The instrument used is the test of learning outcomes in the form of multiple choice questions as well as the activeness sheet of students. The collected data is then analyzed using descriptive statistical analysis. The results indicate that the steps in each phase of the learning model can improve the activities and learning outcomes of students. In cycle I the percentage of learning activities of students is 61.17% with the category quite active and the percentage of learning completeness of students is 46.67%. In cycle II the percentage of learning activities of students has increased to 86.09% with very active category and students' learning outcomes also increased with the percentage of complete is 83.33%. Keywords: Chemical bonding, Learning outcomes, Study activit, Talking chipsAbstrakPenelitian ini adalah penelitian tindakan kelas yang bertujuan untuk mengetahui cara menerapkan langkah-langkah model pembelajaran kooperatif tipe kancing gemerincing (talking chips) di kelas X MIA 3 SMAN 1 Bontomarannu pada materi pokok ikatan kimia. Penelitian ini dilaksanakan sebanyak dua siklus. Instrumen yang digunakan adalah tes hasil belajar berupa soal pilihan ganda serta instrumen lembar keaktifan peserta didik. Data yang terkumpul kemudian dianalisis menggunakan analisis statistik deskriptif. Hasil penelitian menunjukkan bahwa langkah-langkah pada setiap fase model pembelajaran tersebut dapat meningkatkan keaktifan dan hasil belajar peserta didik. Pada siklus I persentase keaktifan peserta didik sebesar 61.17% dengan kategori cukup aktif dan persentase ketuntasan hasil belajar peserta didik sebesar 46.67%. Pada siklus II persentase keaktifan peserta didik mengalami peningkatan menjadi 86.09% dengan kategori sangat aktif dan hasil belajar peserta didik juga meningkat dengan persentase ketuntasan sebesar 83.33%.Kata Kunci: Ikatan kimia, Hasil belajar, Keaktifan belajar, Kancing gemerincing